Ljudska glasba znotraj umetne - Klemenčič, Ivan (Traditiones (Ljubljana), 1999)
The article analyzes a value and hierarchic relationship between folk and art music which enables a one-way incorporation of the first into the latter, but not vice versa. In the period between World Wars I and II there have been heated discussions about the subject. A detailed research based on the example of Slovene music reveals this relationship from the period of Renaissance to modernism.
Keywords: folk music; ljudska glasba; music; glasba